Making cycling irresistible. Lessons from the Netherlands, Denmark, and Germany. - Pucher, John; Buehler, Ralph (My University, 2007)
This paper shows how the Netherlands, Denmark, and Germany have made bicycling a safe, convenient, and practical way to get around their cities. The analysis relies on national aggregate data as well as case studies of large and small cities in each country. The key to achieving high levels of cycling appears to be the provision of separate cycling facilities along heavily traveled roads and at intersections, combined with traffic calming of most residential neighborhoods. Extensive cycling rights of way in the Netherlands, Denmark, and Germany are complemented by ample bike parking, full integration with public transport, comprehensive traffic education and training of both cyclists and motorists, and a wide range of promotional events intended to generate enthusiasm and wide public support for cycling. In addition to their many pro-bike policies and programs, the Netherlands, Denmark, and Germany make driving expensive as well as inconvenient in central cities through a host of taxes and restrictions on car ownership, use, and parking. Moreover, strict land use policies foster compact, mixed-use developments that generate shorter and thus more bikeable trips. It is the coordinated implementation of this multifaceted, mutually reinforcing set of policies that best explains the success of these three countries in promoting cycling. For comparison, the paper portrays the marginal status of cycling in the UK and USA, where only about one percent of trips are by bike. difu
Keywords: Fahrradverkehr; Verkehrspolitik; Verkehrsberuhigung; Förderungsprogramm; Vergleich; Verkehrsmittelwahl; Verkehrsverhalten; Verkehrssicherheit; Individualverkehr; Fahrradförderung; Fahrradnutzung; Fahrradparken; Radverkehrsanteil; Fahrradinfrastruktur; Radverkehrsanlage